« I don’t think that’s the way healthcare for an 85 and an 88-year-old should be done. » L’accès aux services de santé et aux services sociaux des aînés anglophones vivant hors Montréal : état de la situation [thèse de maîtrise, Université de Sherbrooke] - Ethier, Alexandra (Université de Sherbrooke, 2020)
Les aînés anglophones du Québec hors Montréal ont un accès variable aux services de santé et services sociaux (SSSS). C’est pourquoi notre recherche explore l’accès aux SSSS pour les aînés anglophones vivant hors Montréal. Spécifiquement, nous décrivons les facteurs (facilitateurs et barrières) influençant l’accès aux SSSS. Ainsi, nous avons conduit une recherche qualitative de type étude de cas unique imbriquée. Nous avons collecté les données à l’aide d’entretiens semi-dirigés audio-enregistrés, d’un questionnaire sociodémographique et d’un journal de bord. Nous avons transcrit, puis analysé thématiquement les entretiens et avons analysé les données sociodémographiques par statistiques descriptives. Les 10 aînés rencontrés nous ont permis d’identifier 11 facteurs divisés en 6 facilitateurs et 8 barrières influençant l’accès aux SSSS. Les plus signifiants sont la concordance (facilitateur) ou la non-concordance (barrière) de la langue de l’aîné avec le travailleur des SSSS, où la nonconcordance mène à des consentements aux interventions non valides. Également, le facteur présence minoritaire, c’est-à-dire la concentration de la population anglophone, affecte les opportunités sociales des aînés. Ce facteur est un facilitateur lorsque fort et une barrière, lorsque faible. Enfin, des SSSS peu « amis » des aînés anglophones, définis comme un système de SSSS complexe à naviguer lorsque la langue des aînés et leurs caractéristiques personnelles ne sont pas prises en considération, constituent également une barrière. Les résultats de cette recherche informent sur les actions à poser pour faciliter l’accès aux SSSS de ces aînés anglophones et suggèrent des améliorations bénéfiques pour l’ensemble de la population.

Strategies to access health and social services for English-speaking older adults in Quebec: A qualitative case study - Ethier, Alexandra; Carrier, Annie (Canadian Social Work Review, 2023)
Considering that French is the dominant language in Quebec, that relatively few francophone providers of health and social services are able to speak English, and that English-speaking older adults (OAs) have low levels of bilingualism, anglophone OAs are more likely than their francophone peers to face language barriers when accessing health and social services. However, little is known about the strategies English-speaking OAs put into place to overcome the difficulties encountered due to language barriers when they access these services. We therefore aimed to document the strategies used by English-speaking OAs when, due to language barriers, they faced difficulties in accessing health and social services. We conducted a qualitative case study with ten English-speaking OAs in the Eastern Townships in Quebec. Through interviews and document reviews, we collected data which we then analyzed thematically. We identified seven strategies used by English-speaking OAs: investigating for health- and access-related information in English, creating their own services, entering the health and social services system offered in French, entering the health and social services system with help from others, putting the responsibility of overcoming the language barrier on the provider, splitting that responsibility, and taking on the responsibility. Our results highlight a potential burden associated with the involvement of the English-speaking community in enabling English-speaking OAs to access health and social services. Keywords: access, health services, social services, official language minority, language barriers, strategies

Access to health care services: East-End Montreal (Quebec) English-speaking elderly experience [master's thesis, McGill University] - Thomas, Rosemary Hellen. (2008)